RESEARCH OF UNCERTAIN DYNAMIC SYSTEMS OF THE THIRD ORDER BASED ON THE ROOT LOCUS PORTRAITS - A. A. Nesenchuk (Informatika, 2016)
The problem of stability of uncertain interval dynamic systems of the third order is considered. Properties and regularities of the system root locus portrait parameter function behavior at the system stability bound have been discovered, the dependency of the portrait configuration from the values of variable parameters has been shown. The root locus and algebraic stability conditions have been for-mulated. On this basis the algorithm for parametric synthesis of interval systems has been worked out, which allows to calculate the system parameters ensuring its robust stability.